The influence of health education on the selection of birth attendants on the knowledge of pregnant women in Onolimbu Village in 2022 - Rangkuti, Saddiyah; Zaen, Niasty Lasmy (Jurnal EduHealth, 2024)
One of the factors that influence the high maternal mortality rate is the mother's knowledge of birth attendants. The selection of birth attendants is one of the efforts made to seek help in the face of the labor process. The Ministry of Health has mandated that deliveries must be assisted by competent health personnel. The purpose of this study was to determine the effect of health education on the selection of birth attendants on the knowledge of pregnant women in Onolimbu Village in 2022. This type of research uses a pre-experimental design approach with one-group pretest-posttest design. The population in this study were all 32 women of PUS in Onolimbu Village. The sample was taken using the acidental sampling technique. A sample of 22 people was obtained. Bivariate data analysis used the Wilcoxon signed rank test. The results of this study indicate that the mean values are 0.14 (pre) and 0.91 (post). The results of statistical tests using the Wilcoxon test are known that the p value (0.000) < (0.05) means that Ho is rejected. The conclusion of the study is that there is an effect of health education on the selection of birth attendants on the knowledge of pregnant women in Onolimbu Village in 2022. It is recommended for midwives to improve the quality of ANC services through the Delivery Planning Program.